Q. 333.7( 3 Votes )

Find the followin

Answer :

(i) Given that:


=



[∡ (a + b)(a2 – ab + b2) = a3 + b3]


=


(ii) Given that: (x2 βˆ’ 1) (x4 + x2 + 1)


= (x2 βˆ’ 1) [(x2)2 + (x2) (1) + (1)2]


= (x2)3 βˆ’ (1)3


[∡ (a – b) (a2 + ab + b2) = a3 – b3]


= x6 βˆ’ 1


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the vaRS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

If <span lang="ENNCERT Mathematics Exemplar

Show that p – 1 iNCERT Mathematics Exemplar

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the value ofNCERT Mathematics Exemplar

In each of the foRD Sharma - Mathematics